Developing Urban Community Garden Projects - Austen Moore; Amy Harder; Norma Samuel (EDIS)
Community gardens are pieces of land where groups of people grow and maintain vegetable and flower plants. They exist in all types of areas, including neighborhoods, at schools, or on other public or private lands. Community gardens grow food for local consumption or sale and can also be used for teaching gardening and other skills This 7-page fact sheet provides a guide to individuals or groups interested in starting urban community gardens and includes information about how to identify garden sites, build partnerships, engage community members, and develop a project overview. Written by Austen Moore, Amy Harder, and Norma Samuel, and published by the UF Department of Agricultural Education and Communication, March 2013.